Relationship Between The Student Registration Services Communication Process And Student Characteristics - Maharani Imran; Djuara P. Lubis; Basita Ginting Sugihen (Yayasan Ilomata, 2022)
Introduction/Main Objectives: Universities need effective communication with prospective students through various communication channels to attract them to their programs. Background Problems: Public relations universities need to provide maximum service to prospective students in accordance with student characteristics and university communication media. Novelty: Many previous studies have examined the public relations of universities with the theme of image or social media of universities. This study examines the relationship of individual characteristics with the public communication process in universities in terms of use, message content, and frequency. Research Methods: The method used in this study is descriptive correlation with quantitative and qualitative approaches. This study used a quota sample. Hypothesis tests were conducted using spearman rank correlation test. Finding/Results: The results of the study show that the use of communication channels, which has a great influence on the character of students is brochure, the content of the message, which has a great influence on student characteristics is the brochure communication channel. The frequency of communication channels that have a great impact on individual character are verbal messages, Facebook and banner. Conclusion: It is necessary to focus on the increased use of brochure communication channels, the content of brochures and the frequency of verbal messages, Facebook and banners.